FORMULATION AND EVALUATION OF EGG ALBUMIN BASED CONTROLLED RELEASE MICROSPHERES OF METRONIDAZOL - Namdev, Nidhi (International Journal of Current Pharmaceutical Research, 2016)
Objective: The objective of this study was to formulate controlled release microspheres of metronidazole using natural polymer egg albumin. Methods: In this study egg albumin microspheres loaded with metronidazole were prepared by chemical cross linking method with help of glutarldehyde as cross-linking agent. Microspheres were prepared by using different drug/polymer ratios. Egg albumin was used as a release retarding agent in the formulation to get controlled release of metronidazole. Results: The drug-excipients compatibility studies reveal that there is no physical change observed in the drug and egg albumin mixture. Microspheres were found to be spherical, with porous outer skins and quite smooth surfaces when viewed microscopically. Best Results of the carr's index, hausner's ratio as well as angle of repose of the M5 batch were 10.2%, 1.11 and 35.37 respectively Maximum Drug entrapment efficiency (78%) and % yield (94%) was obtained with formulation M5. Drug release for the batch M5 (drug: polymer ratio–1:4) was 77.09% upto 10 h. Conclusion: The hypothesis of this research work i.e. Controlled drug release by using natural biodegradable polymer was well promoted by results of its evaluation. The in vitro release studies showed that drug release was controlled (best with M5 formulation) for more than 10 h. This study reveals the utility of microspheres in extanding the drug release. This may in turn reduces the dosage frequency, thereby improving the patient compliance.